2005
DOI: 10.1097/00004356-200512000-00003
|View full text |Cite
|
Sign up to set email alerts
|

The Usher lifestyle survey: maintaining independence: a multi-centre study

Abstract: Patients with Usher syndrome face a special set of challenges in order to maintain their independence when their sight and hearing worsen. Three different types of Usher (I, II and III) are distinguished by differences in onset, progression and severity of hearing loss, and by the presence or absence of balance problems. In this study 93 Usher patients from seven European countries filled out a questionnaire on maintaining independence (60 patients type I, 25 patients type II, four patients type III and four p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 20 publications
0
36
0
Order By: Relevance
“…Not surprisingly, the second‐largest diagnostic group, after age‐related sensory impairment, was Usher Syndrome. This group of clients has history and a more established identity within the DSI rehabilitation community and their needs have previously been discussed in more detail 39,40 . What emerged from the diagnostic review in Appendix S1 was the large number and variety of other diagnostic combinations that can cause dual impairment, many of which are rarely discussed in the research context.…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, the second‐largest diagnostic group, after age‐related sensory impairment, was Usher Syndrome. This group of clients has history and a more established identity within the DSI rehabilitation community and their needs have previously been discussed in more detail 39,40 . What emerged from the diagnostic review in Appendix S1 was the large number and variety of other diagnostic combinations that can cause dual impairment, many of which are rarely discussed in the research context.…”
Section: Discussionmentioning
confidence: 99%
“…The Usher Lifestyle Survey is a descriptive questionnaire consisting of nine main questions divided into several subquestions on the topic of maintaining independence. This questionnaire was developed in the United Kingdom by Sense 12,13 . In 1980, the Nordic countries agreed to a common definition of domains of independence that are adversely affected in deaf–blindness.…”
Section: Methodsmentioning
confidence: 99%
“…25 Other studies have also shown that Usher syndrome in adults can be associated with stress, anxiety and depression 26–28. There is also evidence that Usher syndrome is linked to decreased social trust24 and increased feelings of social isolation and loneliness 28.…”
Section: Introductionmentioning
confidence: 99%